Averaging in dislocation mediated plasticity. (April 2020) - Le, K.C.; Le, T.H.; Tran, T.M.
Abstract: Starting from the assumption that all possible orientations of grains are equally probable, we evaluate the mean resolved shear stress and strains in polycrystalline bars subjected to axially symmetric tension or compression. The evaluated quantities, in combination with the kinetics of thermally activated dislocation depinning, are used to establish the equation for the stress rate. We then perform a large-scale least-square analysis to identify the physics based parameters of this theory and show that the simulated stress-strain curves for copper, iron and steel agree well with the experiments of Johnson and Cook.